Duties & Responsibilities of Notary Recipient of Minuta Deed of Notary Protocol who has Retired or has Passed Away in Salatiga - Nanda Kurniawan; Amin Purnawan; Ngadino Ngadino (Jurnal Akta, 2020)
This study aims to examine and analyze: 1) Duties and Responsibilities of Notaries as Recipients of the Minuta Deed Protocol. 2) Implementation and Submission of Protocols for Notaries Who Have Retired or Died in the City of Salatiga. The approach method used in this research is the empirical legal approach (sociological) because in this study it examines people in living relationships in society, the study uses empirical facts taken from human behavior, both verbal behavior obtained through interviews and real behavior done through direct observation. The specification is analytic descriptive research. Legal research is focused on examining the compliance of the community, especially notaries as recipients of duties and responsibilities of notaries as recipients of the Minuta Deed Protocol to a legal norm with the aim of measuring whether or not a legal arrangement is effective. In this study, the data source consisted of primary data obtained by researchers through interviews and secondary data obtained through literature studies. Based on the research results it can be concluded that: 1). 2) Constraints in Implementing Duties and Responsibilities of Notary Public as Recipient of Duties and Responsibilities of Notary Public as Recipient of Minuta Protocol, especially in Salatiga City, namely the lack of adequate and adequate space owned by the notary receiving the protocol, the number of protocols that must be accepted, it is not uncommon for the notary receiving protocol to lack a place to store due to limited office space. So it is better if you keep the minuta deed in the form of soft copy, microchip or storage in electronic or digital form, because storing the minuta deeds is more practical and does not take up a lot of space, and makes it easier to maintain and search for the minuta archives if one is needed.